Sport in the tracks and fields of the corona virus: Critical issues during the exit from lockdown - Timpka, T. (Journal of Science and Medicine in Sport, 2020)
COVID-19 is the clinical disease that results from an infection with the new Severe Acute Respiratory Syndrome Coronavirus 2 (SARS-CoV-2).1 In early 2020, the SARS-CoV-2 made its way around the world, with nations having to adopt measures to stop the virus overwhelming hospitals and causing causalities. Social distancing and case isolation have been the foundation of most national strategies, while border restrictions have been used to decrease international travel. These lockdown measures have come at significant cost. Individual citizens` lives and whole economies have been paused. Globally, sport has also been harshly affected by the pandemic lockdown. The Tokyo Olympics 2020 have been moved one year later, with recent comments by global health and infectious disease experts cautioning that even hosting the Olympics in 2021 may be unrealistic.2 The International Olympic Committee (IOC) stated that in a worst case scenario, both the 2020 and 2022 Olympics, in effect, an entire Olympiad, will suffer from the pandemic.3 The aim of this extended letter is to examine the immediate consequences of the pandemic for sports and to discuss some critical issues during the exit from the initial lockdown.